Analysis of Specific and Non-Specific Parameters of Fragant Pandan Leaf Extract In The Bungah Region of Gresik (Pandanus amaryllifolius) - Amilia Putri, Sasti; Anisaus Sholiha, Nur (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Pandanus amaryllifolius leaves are herbal plants known to have various pharmacological activities such as antibacterial, antidiabetic, anticancer, and antioxidant. These activities are supported by the content of active compounds such as flavonoids, saponins, tannins, and alkaloids. This study aims to determine the results of specific and non-specific parameters of pandan leaf extract from Bungah Village, Gresik Regency. The extraction method used maceration with 96% ethanol solvent. The research design used an experimental type. The yield of the extract obtained was 6.45%. In this study, specific parameter tests were carried out which included organoleptic tests and non-specific parameters which included water content tests, total ash content and acid-insoluble ash content. The results of the organoleptic specific parameter test showed that the extract was brown, had a distinctive odor, and had a bitter taste. The results of the non-specific parameter test include a water content of 1.9% ± 0.8 which meets the FHI requirements of no more than 10.8%, but the total ash content of 22.9% ± 6.2 does not meet the requirements set by FHI of no more than 8.9%, and the results of the acid-insoluble ash content of 20.1% ± 77.9 do not meet the requirements set by FHI of no more than 0.2%. Based on the results of the study, the extract of fragrant pandan leaves meets the standards for water content and organoleptic parameters, but does not meet the standards for total ash content and acid-insoluble ash content.